Pendampingan Pembentukan Lembaga Pers Siswa dalam Meningkatkan Literasi Jurnalistik SMA Negeri 2 Kupang - Rindiani, Reza Noersyifa; Nurhadi, Zikri Fachrul (Penerbit Goodwood, 2025)
Purpose: The purpose of this study is to form students' awareness and critical thinking towards social issues that develop in society, as well as to foster students' interest in reading and writing, and to improve students' abilities and skills in the field of journalism. Methodology: The method used in this service is: training in the form of presenting material and implementing the journalism knowledge learned. Result: The results of this journalistic literacy assistance are shown by several changes, such as full support from the school, student enthusiasm in participating in the journalistic literacy program which was followed by the number of students increasing from 17 students to 50 students. Conclusions: This study successfully established the Student Press Institute (LPS) at SMA Negeri 2 Kupang, which is a forum for students to hone their journalistic skills, think critically, and increase their interest in reading and writing. The existence of LPS also encourages active participation of students in expressing opinions and building strong social networks in the school environment. The results of the study showed a significant increase in the number of members, school support, and facilities that support student journalistic activities. Limitations: This study was limited to one school, so the findings and impacts may not be fully applicable to other schools with different conditions. In addition, this study has not evaluated in depth the long-term effectiveness of LPS in improving students' literacy and journalistic skills. External factors such as school curriculum and the level of teacher involvement in supporting LPS have also not been thoroughly analyzed. Contribution: This research can be useful for all high schools that plan to establish a journalism extracurricular activity or simply to implement journalistic literacy practices in the school.